2019
DOI: 10.1103/physrevb.99.054431
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Dzyaloshinskii-Moriya interaction and domain wall velocity through interface intermixing in Ta/CoFeB/MgO

Abstract: The interfacial Dzyaloshinskii-Moriya Interaction (DMI) plays a crucial role in chiral domain wall (DW) motion, favoring fast DW velocities. We explore the effect of interface disorder on DMI and DW dynamics in perpendicular magnetized Ta/CoFeB/MgO thin films. Light He + irradiation has been used to gently engineer interface intermixing on a scale of 0.1 nm. We demonstrate that a slight modification of the Ta/CoFeB interface leads to an increase of the DMI value accompanied by an enhancement of DW velocity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
41
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 43 publications
6
41
0
3
Order By: Relevance
“…Such a system shows great potential not only for SOT based memory devices 15 but also for spin Hall nano-oscillators and spin Hall generation of propagating spin waves owing to its high PMA and large spin Hall angle. 16,17 We show that opposite to the Ta-CoFeB-MgO system, 14,18 a weak intermixing of the bottom W-CoFeB interface leads to a strong reduction of DW pinning and an increase in DW velocity in the creep regime, whereas the DMI value is only slightly reduced. The reduction of DMI is also found to be correlated with the reduction of interface anisotropy.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Such a system shows great potential not only for SOT based memory devices 15 but also for spin Hall nano-oscillators and spin Hall generation of propagating spin waves owing to its high PMA and large spin Hall angle. 16,17 We show that opposite to the Ta-CoFeB-MgO system, 14,18 a weak intermixing of the bottom W-CoFeB interface leads to a strong reduction of DW pinning and an increase in DW velocity in the creep regime, whereas the DMI value is only slightly reduced. The reduction of DMI is also found to be correlated with the reduction of interface anisotropy.…”
mentioning
confidence: 77%
“…These calculations take only the nearest neighbors into account, leading to a gap between simulation results and experimental conditions. In addition, previous studies 13,14 have shown that asymmetric disorder between the bottom and top interfaces in the heavy metal (HM)/ferromagnetic metal (FM)/oxide or HM structure can lead to an increase in the DMI. These studies clearly show that understanding and minimizing the role of interface disorder are crucial for the design of future low power devices based on chiral DW motion and skyrmion manipulation.…”
mentioning
confidence: 99%
“…Figure 5 (a) shows the DW velocity curves as a function of the perpendicular magnetic field strength obtained for biasing times of 1 minute, 2 minutes and 4 minutes (open symbols) indicating a strong reduction of the DW velocity consistent with the observed decrease in D. The curves do not present the typical dependence described by the one dimensional model of DW motion [28], namely a strong decrease of the speed after the Walker field, followed by a linear increase with low mobility, instead they show a saturation of the DW velocity a high magnetic fields. This feature, which has already been observed in a number of materials including Pt/Co [25,29,30], has been attributed to instabilities of the internal structure of the DW above the Walker field, where the annihilation of vertical Bloch lines allows maintaining high velocities after the Walker field [31]. Micromagnetic simulations conducted in order to better understand the mechanism behind the observed velocity reduction are also shown in Fig.…”
Section: Magnetic Domain Wall Motionmentioning
confidence: 65%
“…5 (b) have been obtained with values of D of 1.3 mJ/m 2 , 1.05 mJ/m 2 and 0.74 mJ/m 2 for the samples biased for 1 minute, 2 minutes and 4 minutes, respectively, which are significantly higher than the D values obtained by either BLS or DW motion. Other studies in the literature [30] have shown that intermixing and disorder at the ferromagnetic/heavy metal interface can not only lead to changes in D but can also have a large impact on the value of the DW velocity plateau. A careful analysis of the impact of E-field induced ionic motion on disorder is needed to complete the picture and better understand the discrepancies between the values of D obtained by different methods.…”
Section: Magnetic Domain Wall Motionmentioning
confidence: 94%
“…In earlier reports, the maximum field in which the domains still exist can be used to determine the Dzyaloshinskii-Moriya interaction (DMI) 133,134 . The field-induced evolution of the dendritic domains led to a hysteresis like curve in 138,139 . The larger DMI present in this stack can lead to the stabilisation of the dendritic-like domains.…”
Section: Resultsmentioning
confidence: 99%